Xianyu capsule ameliorates neuroinflammatory and glycerophospholipid metabolism in lithium-pilocarpine-induced acute epilepsy - Yu, Dongsheng; Li, Shuang; Li, Xiaoping; Zhang, Xiaodan; Guo, Danfeng (Frontiers in Nutrition, 2025)
ObjectiveXianyu capsule (XYC) is a commonly used traditional Chinese medicine in the clinical treatment of epilepsy, with significant curative effect and good safety. However, its mechanism of action remains poorly understood. This research employed a multi-omics approach to systematically evaluate the anti-epileptic efficacy of XYC and elucidate its underlying mechanisms.MethodsEpilepsy rat model was established by lithium-pilocarpine hydrochloride injection. XYC was administered and the effects and mechanism was analyzed with H&E and Nissl staining, TUNEL assay, ELISA assay for inflammatory cytokines, 16S rDNA, non-targeted metabolomics and network pharmacology. The potential target were experimentally validated with RT-qPCR and Western blotting analysis.ResultsXYC administration ameliorated the pathological changes and neurons apoptosis of brain hippocampus CA1 region, with reduced MDA and increased SOD and CAT levels in hippocampus, and decreased inflammation cytokine in serum. 16S rDNA sequencing revealed distinct gut microbial restructuring in XYC-treated epileptic models, characterized by phylum-level alterations in lipid-associated taxa (Tenericutes, Patescibacteria, Epsilonbacteraeota, Proteobacteria) and genus-level modulations (Lactobacillus, Ramboutsia, Staphylococcus). Serum metabolomics identified 149 differentially expressed metabolites positively correlated with XYC’s anti-epileptic effects, predominantly enriched in glycerophospholipid metabolic pathways. Network pharmacology identified AKT1, INS, and IL-6 as pivotal mediators of XYC’s therapeutic effects, which were subsequently validated with Western blotting and ELISA assay.ConclusionOur results proved that XYC exerted favorable effect on epilepsy by modulating the gut microbiota and serum lipid metabolic, especially neuroinflammation and glycerophospholipid metabolism by regulating the AKT1, INS and IL-6 expression levels. In addition, targeting neuroinflammatory pathways and modulating glycerophospholipid metabolism may represent a promising therapeutic strategy for epilepsy management.